Prototype Of Moisture Content Meter In Grain Using Esp32 Based On Spreadsheet - Ramadhan, Mochammad Derian; Wisaksono, Arief; Jamaaluddin, Jamaaluddin; Ahfas, Akhmad (Information Technology and Science (ITScience), 2024)
In the process period after the rice is harvested, the rice is then separated from the stalk and referred to as grain which will then be dried. The dried grain aims to reduce the water content, in measuring the water content of the grain, an effective and efficient measurement and database storage tool is needed for users to find out which grain is suitable for processing and can determine the quality of the water content of the grain. The method used in this research uses the RnD (Research And Development) method. In this test using capacitive soil moisture sensor and using database storage in the form of google spreadsheet. The capacitive soil moisture sensor is also calibrated with conventional measuring instruments (Grain Moisture Meter) to find out whether the sensor works properly and accurately. The results in this test found that all components are able to work properly and show an error value <1, the sample reading data will be sent to the database on google spreadsheet so that users can find out the data records in real time and detail.